The influence of viral marketing digital influencers and online consumer reviews on purchase intention - Friedo Hekya Yuland; Eri Besra; Syafrizal (Institute of Computer Science (IOCS), 2023)
This research uses quantitative methods. The population in this study is the people of Padang City with the sample being the people of Padang City who plan to buy Honda brand car products. The sample technique in this study used purposive sampling so that a total sample of 140 respondents was obtained. The test uses structural equation modeling (SEM) with smartPLS 03 software. The analysis covers two-stage assessments; first, construct validity and reliability of each indicator are used to test the measurement model; finally, a model fit to test the causal correlation between latent variables The advancement in communication technology has brought about a new electronic form of word-of-mouth advertising, known as viral marketing. Internet-induced viral marketing is a highly effective tool available to marketers today. Online marketing has been used by various organizations through platforms such as blogs, company websites, and social networking sites. This study aims to determine the influence of Viral Marketing, Digital Influencer, and Online Consumer Review on Purchase Intention of Honda Brio Satya cars in Padang City. The method used in this research is quantitative. The research was conducted from October to December 2022. The population in this research is the community of Padang City. The sample in this research is the community in Padang City who are planning to purchase Honda brand cars. This research used structural equation quality with the concept of path analysis research model that is used to analyze the pattern of relationships between variables with the aim of finding out the direct or indirect effect of the independent variable (exogenous) on the dependent variable (endogenous). The results of this study indicate that there is a significant influence of viral marketing, digital influencers, online consumer reviews on purchase intention